Composition of the Biofilm Matrix of Cutibacterium acnes Acneic Strain RT5 - Gannesen, Andrei V.; Zdorovenko, Evelina L.; Botchkova, Ekaterina A.; Hardouin, Julie; Massier, Sebastien; Kopitsyn, Dmitry S.; Gorbachevskii, Maxim V.; Kadykova, Alexandra A.; Shashkov, Alexander S.; Zhurina, Marina V.; Netrusov, Alexander I.; Knirel, Yuriy A.; et al. (Frontiers in Microbiology, 2019)
In skin, Cutibacterium acnes (former Propionibacterium acnes) can behave as an opportunistic pathogen, depending on the strain and environmental conditions. Acneic strains of C. acnes form biofilms inside skin-gland hollows, inducing inflammation and skin disorders. The essential exogenous products of C. acnes accumulate in the extracellular matrix of the biofilm, conferring essential bacterial functions to this structure. However, little is known about the actual composition of the biofilm matrix of C.acnes. Here, we developed a new technique for the extraction of the biofilm matrix of Gram-positive bacteria without the use of chemical or enzymatic digestion, known to be a source of artefacts. Our method is based on the physical separation of the cells and matrix of sonicated biofilms by ultracentrifugation through a CsCl gradient. Biofilms were grown on the surface of cellulose acetate filters and the biomass was collected without contamination by the growth medium. The biofilm matrix of the acneic C. acnes RT5 strain appears to consist mainly of polysaccharides. The ratio of the main matrix components was: 62.6% polysaccharides, 9.6% proteins, 4.0% DNA, and 23.8% other compounds (porphyrins precursors and other). The chemical structure of the major polysaccharide was determined using a nuclear magnetic resonance technique, the formula being →6)-α-D-Galp-(1→4)-β-D-ManpNAc3NAcA-(1→6)-α-D-Glcp-(1→4)-β-D-ManpNAc3NAcA-(1→3)-β- GalpNAc-(1→. We detected 447 proteins in the matrix, of which the most abundant were the chaperonin GroL, the elongation factors EF-Tu and EF-G, several enzymes of glycolysis, and proteins of unknown function. The matrix also contained more than 20 hydrolases of various substrata, pathogenicity factors, and many intracellular proteins and enzymes. We also performed surface-enhanced Raman spectroscopy analysis of the C. acnes RT5 matrix for the first time, providing the SERS profiles of the C. acnes RT5 biofilm matrix and biofilm biomass. The difference between the matrix and biofilm biomass spectra showed successful matrix extraction rather than simply the presence of cell debris after sonication. These data show the complexity of the biofilm matrix composition and should be essential for the development of new anti-C. acnes biofilms and potential anti-biofilm drugs.